End of Meeting Report - ISPC 8 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2013)
The eighth ISPC meeting was attended by 42 participants on 10th and 11th September 2013. The report annexes contain the list of participants as well as the final agenda for the meeting. An ISPC closed session on strategic issues was held on 9th September 2013.